THE FIRST EDITION OF IMMANUEL KANT’S LECTURES ON MORALITY AND RELIGION IN POLISH EDITION BY KRZYSZTOF CELESTYN MRONGOWIUSZ - Купш, Томаш (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2014)
The article researches the First Edition of Immanuel Kant’s Lectures on Morality and Religion in Polish Edition by Krzysztof Celestyn Mrongowiusz.